Exploring the construction of a youth mental health campus ecosystem integrating research-practice teaching - Gao, Tao (Frontiers in Public Health, 2025)
This study explores the construction of a youth mental health-promoting campus ecosystem based on integrated research-practice teaching. In response to the fragmentation of traditional mental health education in Chinese universities, the model incorporates ecosystem theory, embodied cognition, and multi-agent collaboration to build a four-dimensional support system: curriculum-practice integration, internal-external stakeholder synergy, environmental optimization, and institutional sustainability. Through immersive practices like psychodrama, mind mapping, and mindful walking, students’ psychological capital and self-regulation abilities are enhanced. The model emphasizes collaboration across psychological, educational, and managerial units, as well as coordination with families, communities, medical institutions, and enterprises. By combining physical space design with digital tracking platforms, the ecosystem enables all-scenario psychological support. Challenges such as insufficient longitudinal validation, ethical concerns in AI-driven interventions, and uneven resource allocation remain. This study provides a localized and actionable framework for advancing youth mental health in higher education, supporting a shift from crisis intervention to positive psychological development.